What is Florida-Friendly Landscaping™? - Esen Momol; Michael Scheinkman; Michael Thomas; Tom Wichman; Gail Hansen; Claire Lewis; Jen Marvin; Lynn Barber; Tiare Silvasy; Terra Freeman; Tina McIntyre; Emily Brown; et al. (EDIS)
Florida-Friendly Landscaping™ (FFL) provides science-based landscape design and plant selection practices for installing and maintaining resilient, aesthetically pleasing landscapes. Once established, FFL landscapes require little, if any, irrigation, fertilizer, or pesticides. This new 7-page publication of the UF/IFAS Environmental Horticulture Department provides a brief overview of the FFL program, outreach, and requirements.